(untitled) (Research, Society and Development, 2021)
Dietary fatty acids may influence the development of the digestive tract and initial activation of digestive enzymes in fish. The objective of this study was to evaluate the effect of the diet lipid profile on ontogeny and activity of digestive enzymes in silver catfish post larvae fed practical diets. Five diets were tested, replacing broiler liver by soybean protein concentrate (SPC) or fish meal (FM): Standard, 15SPC, 30SPC, 15FM and 30FM. The enzymatic activity of fish was analyzed from 32 Hours after fertilization (Haf). Were analysed acid protease, trypsin, chymotrypsin, lipase, amylase and maltase. The development of the digestive system was analyzed from first feeding up to 28 days by histological techniques. The enzymatic activity presented peaks for the post-larvae fed with the 15SPC diet and fish fed with diet 15FM showed best growth. The development of the digestive system did not suffer damage from the diets offered. Post-larvae fed the 30SPC diet showed reduced development of the digestive tract. The diet 15FM provide good lipid profile for silver catfish post larvae.